Two new species of Homidia (Collembola, Entomobryidae) and a key to species in the genus from Zhejiang Province, China - Pan, Zhi-Xiang (Zootaxa, 2015)
Two new species of Homidia are described from Yandang Mountain, China: H. yandangensis sp. nov. and H. quadrimaculata sp. nov. The new species are diagnosed by their unique colour patterns, the number of macrochaetae on areas A8–10 of abdominal segment IV, the relative position of specialised microchaetae/specialised ordinary chaetae on abdominal segment I and specialised ordinary chaetae/macrochaeta m3 on abdominal segment V. Specimens from two localities of H. yandangensis sp. nov. differ in the macrochaeta a5 on area A9 of abdominal segment IV. Descriptions of the subadult dorsal thoracic and abdominal chaetotaxy of H. yandangensis sp. nov. and a key to species of Homidia from Zhejiang Province are provided here.